The Evaluation of Integrated Disease Management of Rice Plants (Oryza sativa L.) In East Buay Madang District, Ogan Komering Regency, South Sumatra (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Rice is a staple food source for people in Indonesia Rice plants (Oryza sativa L.) are one type of hydrophytic spermatopyta plant. The method used in this research is the survey method, which involves directly visiting the land and conducting surveys in several food crop fields in Buay Madang Timur District, Oku Timur Regency. Observation of farmers' fields by observing disease intensity and the application of the concept of integrated pest and disease control. Additionally, by documenting the symptoms of disease attack and recording the results obtained through direct land observations. The results showed the calculation of the incidence of blast disease attacks in Srimulyo Village on land 1 to land 10 including the moderate attack category which is 44%, land 11 to 20 the lowest attack category is 20% and the category of moderate attack percentage is 46% and on land 20 to 30 the category of moderate attack with a percentage of 42%. As well as based on the calculation of the intensity of blast disease attack in Srimulyo Village on the 1st land to the 10th land including the mild attack category which is 15.5%, while on land 11 to 20 the mild attack category with a percentage of 19% while on land 20 to 30 the mild attack attack category with a percentage of 15.6%.